The Effect of Innovative Behavior, Skills, and Communication on the Academic Achievement of Management Study Program Students in Batam City - Siregar, Rendi Habli Rahman; Sabri, Sabri; Yusuf , Muhammad (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
Purpose. This study aims to analyze the effect of innovative behavior, skills, and communication on the academic achievement of Management Study Program students in Batam City. Academic achievement represents an important indicator of students’ learning outcomes and reflects their ability to understand and apply knowledge gained during the educational process. Various individual competencies may contribute to students’ academic performance, including their capacity to generate innovative ideas, develop learning-related skills, and communicate effectively in academic environments. Innovative behavior encourages students to explore creative approaches in solving academic problems, while skills support students in managing learning activities and academic responsibilities. Communication competence also facilitates interaction, discussion, and collaboration in the learning process. Therefore, understanding the role of these factors is important for improving students’ academic achievement in higher education. Materials and methods. This study employed a quantitative explanatory research design using a survey method. The population consisted of Management Study Program students in Batam City, with a total sample of 98 respondents selected for the study. Data were collected using a structured questionnaire measured with a five-point Likert scale. The research instrument was first tested for validity and reliability to ensure accurate and consistent measurements. Data analysis was conducted using SPSS version 26. Several statistical procedures were applied, including classical assumption tests and multiple linear regression analysis. Hypothesis testing was carried out using t-tests to determine partial effects, an F-test to examine the simultaneous influence of the independent variables, and the coefficient of determination (R²) to evaluate the explanatory power of the regression model. Results. The findings show that innovative behavior has a positive and statistically significant effect on students’ academic achievement (Sig.=0.000). Skills also demonstrate a positive and significant influence on academic achievement (Sig.=0.002). In contrast, communication does not show a statistically significant effect on academic achievement (Sig.=0.137). The simultaneous analysis indicates that innovative behavior, skills, and communication collectively have a significant influence on academic achievement (F-test Sig.=0.000). The regression model also shows a high explanatory power with a coefficient of determination (R² = 0.921), indicating that approximately 92.1% of the variation in students’ academic achievement can be explained by the independent variables included in the model. Conclusions. The results highlight the importance of innovative behavior and learning-related skills in improving students’ academic achievement. Although communication did not demonstrate a significant effect in this study, it remains an important element that supports interaction and collaboration in academic environments. Higher education institutions are therefore encouraged to develop learning strategies that promote creativity, skill development, and active participation in order to enhance students’ academic performance.